Peran Digital Payment Dalam Mendorong Pertumbuhan Ekonomi Digital di Indonesia - Sari, Rasidah Novita; Hasanah, Nurul; Septiani, Nazwa; Syahda, Fidela (Madani: Jurnal Ilmiah Multidisiplin, 2025)
This study aims to analyze in depth the role of digital payments in driving the growth of the digital economy in Indonesia. Along with the rapid development of information technology, digital payments have become the backbone that revolutionizes conventional payment systems, powered by ease of access, transaction speed, security, and cost efficiency. The pandemic period of 2020 accelerated the momentum of digital payment adoption in Indonesia. The focus of the study includes analyzing the impact of digital payments on increasing financial inclusion, increasing efficiency and innovation in economic transactions, as well as its contribution to increasing the competitiveness of SMEs in the digital ecosystem. The research method uses a qualitative approach with secondary data from supporting journals and other relevant sources. The research results are expected to provide a comprehensive understanding as well as strategic policy recommendations to optimize the role of digital payments for the realization of an inclusive, sustainable, and globally competitive Indonesian digital economy. The types of digital payments discussed include Quick Response Code Indonesia Standard (QRIS), E-Wallet, and M-Banking, each of which plays a crucial role in this transformation. Research also highlights the benefits and challenges of using blockchain technology in the security of digital transaction data.